2019
DOI: 10.1021/acs.jpclett.9b01690
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Dynamics of Concentrated Silica-PNIPAm Nanogels

Abstract: We present the structure and dynamics of highly concentrated core–shell nanoparticles composed of a silica core and a poly­(N-isoproylacrylamide) (PNIPAm) shell suspended in water. With X-ray photon correlation spectroscopy, we are able to follow dynamical changes over the volume phase transition of PNIPAm at LCST = 32 °C. On raising the temperature beyond LCST, the structural relaxation times continue to decrease. The effect is accompanied by a transition from stretched to compressed exponential shape of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 61 publications
(99 reference statements)
2
11
0
Order By: Relevance
“…Analysis of structure and dynamics of pure PNIPAm nanogels and silica-PNIPAm core-shell systems showed that below a critical dose in the range of 10 5 Gy the dynamics of dense systems could be obtained. This threshold is similar to the ones observed at storage-ring based experiments [133], proving that similar models are valid for both type of experiments.…”
Section: Role Of Sase Fluctuationssupporting
confidence: 84%
See 1 more Smart Citation
“…Analysis of structure and dynamics of pure PNIPAm nanogels and silica-PNIPAm core-shell systems showed that below a critical dose in the range of 10 5 Gy the dynamics of dense systems could be obtained. This threshold is similar to the ones observed at storage-ring based experiments [133], proving that similar models are valid for both type of experiments.…”
Section: Role Of Sase Fluctuationssupporting
confidence: 84%
“…Several XPCS studies have recently studied the phase behaviour of PNIPAm-based colloidal suspension. Frenzel et al [133] used a core-shell systems of a silica core and PNIPAm shell. In a densely-packed system, the relaxation rate showed an anomalous q −3 -behaviour together with a compressed g 2 function below the LCST that might be connected to the chain-dynamics of the polymer.…”
Section: Phase Behaviour Of Soft Colloidsmentioning
confidence: 99%
“…Therefore, besides the volume fraction the phase of such a microgel dispersion depends on the temperature T as well. Above the LCST, the particles become attractive, promoting the formation of a colloidal gel at high volume fractions [16][17][18][19][20][21][22][23][24][25][26][27].…”
mentioning
confidence: 99%
“…X-ray photon correlation spectroscopy (XPCS) is a very powerful and well established tool to investigate slow dynamics of various complex disordered systems in condensed matter, such as colloids (Dierker et al, 1995;Grü bel & Zontone, 2004;Li et al, 2014), polymers (Lehmkü hler et al, 2018;Frenzel et al, 2019), capillary waves (Gutt et al, 2003), metallic glasses (Ruta et al, 2012;Evenson et al, 2015), molecular glasses (Chushkin et al, 2012), charge-density waves (Shpyrko et al, 2007) and water (Perakis et al, 2017(Perakis et al, , 2018. XPCS is derived from well established visible photon correlation spectroscopy (PCS) (Provencher, 1979;Dorfmü ller, 1992;Cipelletti & Weitz, 1999), where a visible laser acts as a coherent source.…”
Section: Introductionmentioning
confidence: 99%